Genetics and Improvement of Barley Malt Quality - Zhang, Guoping; Li, Chengdao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Genetics and Improvement of Barley Malt Quality presents up-to-date developments in barley production and breeding. The book is divided into nine chapters, including barley production and consumption, germplasm and utilization, chemical composition, protein and protein components, carbohydrates and sugars, starch degrading enzymes, endosperm cell walls and malting quality, genomics and malting quality improvement, and marker-assisted selection for malting quality. The information will be especially useful to barley breeders, malsters, brewers, biochemists, barley quality specialists, molecular geneticists, and biotechnologists. This book may also serve as reference text for post-graduate students and barley researchers. The authors for each chapter are the experts and frontier researchers in the specific areas. Professor Guoping Zhang is a barley breeder and crop physiologist in Department of Agronomy, Zhejiang University of China. Dr. Chengdao Li is a senior molecular geneticist and barley breeder in Department of Agriculture & Food, Western Australia. He is also an adjunct professor in Murdoch University of Australia and Zhejiang University of China.
Barley Production and Consumption -- Barley Germplasm and Utilization -- Chemical Composition in Barley Grains and Malt Quality -- Identification of Barley Varieties by Protein Profiling -- ?-glucans and Arabinoxylans -- The Properties and Genetics of Barley Malt Starch Degrading Enzymes -- The Role of Endosperm Cell Walls in Barley Malting Quality -- Barley Genomics and Malting Quality Improvement -- Genetic Improvement of Malting Quality through Conventional Breeding and Marker-assisted Selection.
Keywords: Life sciences; Food science; Agriculture; Botany; Plant breeding; Life Sciences; Plant Sciences; Plant Genetics & Genomics; Agriculture; Food Science